THEORETICAL AND METHODOLOGICAL PRINCIPLES OF FORMING AN EFFECTIVE MANAGEMENT SYSTEM FOR INNOVATIVE ACTIVITIES OF ENTERPRISES - Titenko, Zoia (Current Problems of Sustainable Development, 2026)
The article explores the theoretical and methodological principles of managing the innovative activities of enterprises in modern conditions of economic transformation. In the process of research, the essence of innovative activity as a purposeful process of formation, selection and implementation of innovations, which can be both the result of internal research work of the enterprise and the result of external technology transfer, is revealed. It is substantiated that the effectiveness of innovative activity largely depends on the available resource potential of the enterprise, the level of its organizational development and the ability to adapt to a changing external environment. The factors influencing the innovative activities of enterprises are investigated. It is established that it is advisable to divide them into internal and external. Internal factors form the innovative potential of the enterprise and determine its ability to create and implement innovations. External factors characterize the conditions of the enterprise’s functioning in the external environment and include state innovation policy, legal regulation, economic conditions, the level of scientific and technological progress and globalization processes. Modern scientific approaches to the interpretation of the management of innovative activities of enterprises are summarized. A generalized structural model of the enterprise innovation management system is proposed, which includes input, management, process and output subsystems with feedback. Such a model allows ensuring the integrity of the innovation process, coordination of management functions and adaptation of the enterprise to changes in the external environment. It is substantiated that the innovation management system should be based on the principles of complexity, systematicity, flexibility and strategic orientation. Its implementation allows optimizing the use of enterprise resources, increasing the efficiency of innovation processes and ensuring the achievement of long-term competitive advantages. It has been proven that increasing the innovative activity of enterprises ensures an increase in the efficiency of their activities and their financial stability.
Keywords: innovative activity; enterprises; management; efficiency of activity; financial security